Insights into coastal microbial antibiotic resistome through a meta-transcriptomic approach in Yucatan - Guillén-Chable, Francisco; Avila Castro, Luis Alejandro; Rodríguez-Escamilla, Zuemy; Martínez-Núñez, Mario Alberto (Frontiers in Microbiology, 2022)
Antibiotic resistance (AR) is one of the greatest human and clinical challenges associated with different pathogenic organisms. However, in recent years it has also become an environmental problem due to the widespread use of antibiotics in humans and in livestock activities. The ability to resistance to antibiotics comes from antibiotic resistance genes (ARGs) and our understanding of their presence in coastal environments is still limited. Thus, we assessed the composition and abundance of ARGs through an analysis of high-throughput meta-transcriptomic sequences to explore the microbial resistome of four sites of the Yucatan coast. In total, 6952 ARGs were uncovered, which participate in the resistance to tetracycline, macrolide, rifamycin, fluoroquinolone, phenicol, aminoglycoside, cephalosporin and other antibiotics. The action mechanisms of these ARGs were mainly efflux pump, antibiotic target alteration and antibiotic target replacement. Similar ARGs were detected in the samples but show dissimilar enrichment levels. With respect to the sampling sites, the ARGs were present in all the samples collected, either from preserved or contaminated areas. Importantly, sediments of the preserved area of Dzilam presented the second highest level of ARGs detected, probably as a consequence of the antibiotics dragged to the coast by submarine groundwater discharge. In general, the resistance to a single antibiotic was greater than multiresistance, both at the level of gene and species; and multiresistance in organisms is acquired mainly by recruiting different monoresistance genes. To our knowledge, this is the first study that describes and compares the resistome of different samples of the Yucatan coast. This study contributes to generating information about the current state of antibiotic resistance on the Yucatan coasts for a better understanding of ARGs dissemination and could facilitate the management of ARGs pollution in the environment.